1992
DOI: 10.1007/bf01474724
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive neutral vector meson production in hadronicZ 0 decays

Abstract: Results are reported of a study of neutral vector meson production in multihadronic Z 0 decays in the OPAL experiment at LEP. Pions and kaons have been identied by specic ionisation energy loss and K and K + K mass spectra have been tted, in bins of the scaled momentum variable x p , t o combinations of resonance signals and non-resonant backgrounds. Rates are given for K (892) 0 and (1020), and production cross sections are compared to the predictions of Monte Carlo models. Overall multiplicities have been de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Previous measurements showed that ρ 0 -meson peaks reconstructed in the π + π − decay channel are distorted: the central value (mass) was shifted to lower values by tens of MeV/c 2 . This phenomenon was studied in detail at LEP [2][3][4][5] and was also observed at RHIC [6].…”
Section: Contributions From ρ 0 F 0 (980) and F 2 (1270)mentioning
confidence: 93%
See 1 more Smart Citation
“…Previous measurements showed that ρ 0 -meson peaks reconstructed in the π + π − decay channel are distorted: the central value (mass) was shifted to lower values by tens of MeV/c 2 . This phenomenon was studied in detail at LEP [2][3][4][5] and was also observed at RHIC [6].…”
Section: Contributions From ρ 0 F 0 (980) and F 2 (1270)mentioning
confidence: 93%
“…Due to its very short lifetime (τ ∼ 1.3 fm/c) the ρ(770) 0 meson is well suited to study various properties of the interaction dynamics in nucleon-nucleon and heavy-ion collisions [1]. Previous measurements at the Large Electron-Positron Collider (LEP) [2][3][4][5] and the Relativistiv Heavy Ion Collider (RHIC) [6] showed that properties of ρ(770) mesons reconstructed in the two-pion decay channel are modified in highenergy hadronic interactions and e + e − annihilation. At low momentum, reconstructed ρ(770)-meson peaks were found to be significantly distorted from the p-wave Breit-Wigner shape.…”
Section: Introductionmentioning
confidence: 99%
“…At CERN-LEP, OPAL, ALEPH and DELPHI the ρ 0 was measured in inclusive e + e − reactions at √ s = 90 GeV [9][10][11][12]. Even though OPAL never reported the value of the ρ 0 mass, OPAL reported a shift on the position of the ρ 0 peak by approximately −70 MeV/c 2 at low x p , where x p is the ratio between the meson and the beam energies, and no shift at high x p (x p ∼ 1) [9,10]. OPAL also reported a shift in the position of the ρ ± peak from −10 to −30 MeV/c 2 , which was consistent with the ρ 0 measurement [11].…”
Section: ρ 0 Mass Shifts At Rhic Cern-lebc-ehs and Cern-lepmentioning
confidence: 99%
“…Bose-Einstein correlations were used to describe the shift on the position of the ρ 0 peak. However, high (even unphysical) chaocity parameters (λ ∼ 2.5) were needed [9,10,12]. .…”
Section: ρ 0 Mass Shifts At Rhic Cern-lebc-ehs and Cern-lepmentioning
confidence: 99%
See 1 more Smart Citation